Comparison of Cell Proliferation, Protein, and Glucose Metabolism in Musculoskeletal Tumors in a PET Study. (16th June 2011) - Tian, Mei; Zhang, Hong; Endo, Keigo
Abstract : 11 C-choline and 18 F-FAMT are known to correlate with tumor cell proliferation and amino acid metabolism. We investigated the ability of 11 C-Choline and 18 F-FAMT PET in diagnosis of musculoskeletal tumors in thirty-six patients in comparison of 18 F-FDG PET. 11 C-Choline and 18 F-FDG PET were positive in all the malignant tumors (n=13 ), whereas 18 F-FAMT was positive in 11 tumors. The mean SUVs for malignant tumors were significantly higher than those for benign lesions in all three tracers imaging. A moderate correlation was found between 11 C-Choline and 18 F-FDG (r=0.540, P < .05 ), or 18 F-FAMT and FDG (r=0.596, P < .05 ). The diagnostic sensitivity and specificity for malignancy were 91.7% and 71.4%, respectively, using 11 C-choline with a SUV cut-off of 2.69. The sensitivity and specificity of 18 F-FAMT for malignancy were 66.7% and 85.7%, respectively, using a SUV cut-off of 1.26. For 18 F-FDG, using a SUV cut-off of 2.77, the sensitivity and specificity were 83.3% and 71.4%, respectively. According to ROC analysis, the ROC curves for 11 C-Choline, 18 F-FAMT, and 18 F-FDG were 0.855, 0.734, and 0.847, respectively. 11 C-Choline PET is superior in the visualization of musculoskeletal tumors with high contrast imaging, whereas the combination of 18 F-FAMT and 18 F-FDG PET provides valuable information for the preoperative planning in patients with musculoskeletal tumors.